Targeting the cannabinoid system to counteract the deleterious effects of stress in Alzheimer’s disease - Shade, Ronnie D.; Ross, Jennifer A.; Van Bockstaele, Elisabeth J. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease is a progressive neurodegenerative disorder characterized histologically in postmortem human brains by the presence of dense protein accumulations known as amyloid plaques and tau tangles. Plaques and tangles develop over decades of aberrant protein processing, post-translational modification, and misfolding throughout an individual’s lifetime. We present a foundation of evidence from the literature that suggests chronic stress is associated with increased disease severity in Alzheimer’s patient populations. Taken together with preclinical evidence that chronic stress signaling can precipitate cellular distress, we argue that chronic psychological stress renders select circuits more vulnerable to amyloid- and tau- related abnormalities. We discuss the ongoing investigation of systemic and cellular processes that maintain the integrity of protein homeostasis in health and in degenerative conditions such as Alzheimer’s disease that have revealed multiple potential therapeutic avenues. For example, the endogenous cannabinoid system traverses the central and peripheral neural systems while simultaneously exerting anti-inflammatory influence over the immune response in the brain and throughout the body. Moreover, the cannabinoid system converges on several stress-integrative neuronal circuits and critical regions of the hypothalamic-pituitary-adrenal axis, with the capacity to dampen responses to psychological and cellular stress. Targeting the cannabinoid system by influencing endogenous processes or exogenously stimulating cannabinoid receptors with natural or synthetic cannabis compounds has been identified as a promising route for Alzheimer’s Disease intervention. We build on our foundational framework focusing on the significance of chronic psychological and cellular stress on the development of Alzheimer’s neuropathology by integrating literature on cannabinoid function and dysfunction within Alzheimer’s Disease and conclude with remarks on optimal strategies for treatment potential.